Human Talent Management and Job Performance: A Relational Study in a Peruvian Security Sector Company - Apaza Inca, María Fernanda; Chipana Cayalta, Valeria Aurora; Coaguila Mayanaza, Dante Vidal (LACCEI, 2025)
Human Talent Management (HTM) plays a strategic role in enhancing job performance (JP) and organizational productivity. This study aimed to determine the relationship between HTM and JP in a security sector company located in Ica, Peru. A quantitative approach was adopted, with a relational level and a non-experimental, cross-sectional design. The sample was census-based and consisted of 74 intentionally selected employees who answered structured questionnaires. Descriptive results showed that 55.4% of participants perceived HTM as poor, 21.6% as fair, and 23.0% as good. Among those who rated HTM poorly, 36.5% reported low JP, and only 8.1% reported high JP. Inferential analysis revealed a positive and statistically significant correlation between HTM and JP (ρ = 0.648; p < 0.001). Significant associations were also found in the dimensions of Talent Attraction (ρ = 0.548), Talent Development (ρ = 0.600), and Talent Retention (ρ = 0.648), all with p-values < 0.001. It is concluded that effective human talent management is directly and significantly related to higher levels of job performance. The implementation of comprehensive strategies focused on talent attraction, continuous training, and employee retention is recommended to strengthen human capital and enhance business competitiveness.